2016
DOI: 10.1038/srep35567
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the circadian clock protein complex composed of KaiB and KaiC by inverse contrast-matching small-angle neutron scattering

Abstract: The molecular machinery of the cyanobacterial circadian clock consists of three proteins: KaiA, KaiB, and KaiC. Through interactions among the three Kai proteins, the phosphorylation states of KaiC generate circadian oscillations in vitro in the presence of ATP. Here, we characterized the complex formation between KaiB and KaiC using a phospho-mimicking mutant of KaiC, which had an aspartate substitution at the Ser431 phosphorylation site and exhibited optimal binding to KaiB. Mass-spectrometric titration data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…3, C and D). Consistent with a role in cooperative assembly of the KaiB-KaiC hexamer (50, 53), an R23A mutation in KaiB As (superscript “As” denotes proteins from Anabaena sp.) reduced its binding affinity for KaiC As (54).…”
Section: Kaib Forms a Hexameric Ring On The CI Domains Of Kaicmentioning
confidence: 86%
“…3, C and D). Consistent with a role in cooperative assembly of the KaiB-KaiC hexamer (50, 53), an R23A mutation in KaiB As (superscript “As” denotes proteins from Anabaena sp.) reduced its binding affinity for KaiC As (54).…”
Section: Kaib Forms a Hexameric Ring On The CI Domains Of Kaicmentioning
confidence: 86%
“…It has been demonstrated that KaiB-KaiC complex formation is dependent on the phosphorylation state of KaiC. [40][41][42][43][44][45][46] For example, the recombinant KaiB protein associates with the WT or hyperphosphomimic KaiC protein in the absence of KaiA in vitro, whereas it associates much less with KaiC AA44,46 . Thus, complex formation between KaiB and KaiC would be important for generating the kaiA-less damped oscillation.…”
Section: Resonance Of Damped Oscillation In Response To External Cuesmentioning
confidence: 99%
“…This technique was pioneeringly applied to determine the spatial arrangements of 30 S ribosomal subunits [4] and recently sophisticated as exemplified by the application to quaternary structure analyses of a variety of protein complexes [5] , [6] , [7] , [8] . Deuteration-assisted SANS data in conjunction with crystallographic data has thus facilitated 3D modelling of quaternary structure views of protein complexes like the circadian clock protein complex, KaiB and KaiC [9] , and the large dodecameric aminopeptidase TET [10] .…”
Section: Introductionmentioning
confidence: 99%